3-Phase Brushless Permanent-Magnet Motor Control for Hybrid Electric Vehicle In-Wheel Motor - Mohd Farizol Fuzmi Bin Mohd Bakhi, Mohd Farizol Fuzmi (Universiti Teknologi Petronas, 2010)
This report discusses the project done by the author on the proposed topic, which is 3-Phase Brushless Permanent-Magnet Motor Control for Hybrid Electric Vehicle In-Wheel Motor. The project is about applying a 3-phase brushless in-wheel motor (IWM) to drive the rear wheels of a conventional vehicle based on the hybrid electric vehicle technology. The hybrid electric vehicle achieves better fuel economy than a conventional vehicle.